Analisis Sistem Informasi Akuntansi Penerimaan Kas Dan Pengeluaran Kas Pada PT. Aura Pesona Wisata - Muhammad Abdul Qadir Jailani; Muslimin (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
This research aims to determine, study and test the application and constraints of the accounting information system for cash receipts and disbursements at PT. Aura Pesona Wisata. This research uses a qualitative descriptive method with a case study design. The results of this research show the application of the accounting information system for cash receipts and disbursements at PT. Aura Pesona Wisata is still not running effectively because it still uses a manual system for recording, and the problem that often occurs in the cash receipts and disbursements accounting information system is miscommunication due to multiple functions or tasks within the company.